HLA-B*57 Micropolymorphism shapes HLA allele-specific epitope immunogenicity, selection pressure, and HIV immune control. - Kloverpris, H; Stryhn, A; Harndahl, M; van der Stok, M; Payne, R; Matthews, P; Chen, F; Riddell, L; Walker, B; Ndung'u, T; Buus, S; Goulder, P (2012)
The genetic polymorphism that has the greatest impact on immune control of human immunodeficiency virus (HIV) infection is expression of HLA-B*57. Understanding of the mechanism for this strong effect remains incomplete. HLA-B*57 alleles and the closely related HLA-B*5801 are often grouped together because of their similar peptide-binding motifs and HIV disease outcome associations. However, we show here that the apparently small differences between HLA-B*57 alleles, termed HLA-B*57 micropolymorphisms, have a significant impact on immune control of HIV. In a study cohort of >2,000 HIV C-clade-infected subjects from southern Africa, HLA-B*5703 is associated with a lower viral-load set point than HLA-B*5702 and HLA-B*5801 (medians, 5,980, 15,190, and 19,000 HIV copies/ml plasma; P = 0.24 and P = 0.0005). In order to better understand these observed differences in HLA-B*57/5801-mediated immune control of HIV, we undertook, in a study of >1,000 C-clade-infected subjects, a comprehensive analysis of the epitopes presented by these 3 alleles and of the selection pressure imposed on HIV by each response. In contrast to previous studies, we show that each of these three HLA alleles is characterized both by unique CD8(+) T-cell specificities and by clear-cut differences in selection pressure imposed on the virus by those responses. These studies comprehensively define for the first time the CD8(+) T-cell responses and immune selection pressures for which these protective alleles are responsible. These findings are consistent with HLA class I alleles mediating effective immune control of HIV through the number of p24 Gag-specific CD8(+) T-cell responses generated that can drive significant selection pressure on the virus.